Photoelectrocatalytic Degradation of Sodium Oxalate by TiO2/Ti Thin Film Electrode. (5th March 2012) - Chang, Chen-Yu; Hsieh, Yung-Hsu; Chen, Yu-Ying
Abstract : The photocatalytically active TiO2 thin film was deposited on the titanium substrate plate by chemical vapor deposition (CVD) method, and the photoelectrocatalytic degradation of sodium oxalate was investigated by TiO2 thin film reactor prepared in this study with additional electric potential at 365 nm irradiation. The batch system was chosen in this experiment, and the controlled parameters were pH, different supporting electrolytes, applied additional potential, and different electrolyte solutions that were examined and discussed. The experimental results revealed that the additional applied potential in photocatalytic reaction could prohibit recombination of electron/hole pairs, but the photoelectrocatalytic effect was decreased when the applied electric potential was over 0.25 V. Among the electrolyte solutions added, sodium sulfate improved the photoelectrocatalytic effect most significantly. At last, the better photoelectrocatalytic degradation of sodium oxalate occurred at pH 3 when comparing the pH influence.